Handbook of Open, Distance and Digital Education 2022
DOI: 10.1007/978-981-19-0351-9_45-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital Information and Library Services in ODDE

Abstract: This chapter is anchored on Collaboration being a new construct in the Digital Library Reference Model proposed by the DELOS Network of Excellence on Digital Libraries. The chapter argues that distance learning library services will be significantly enhanced with a collaboratively implemented digital library service taking into cognizance the role of collaboration in strategic planning and policy development, provision of digital collections and information services, and technological infrastructure and skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The availability of support services and students' technological abilities or skills are key to the success of distance learning. One of the most important support systems for guaranteeing effective online or distance education is information services (Owusu-Ansah and Bubuama, 2015;Yeboah et al, 2020). It has been suggested that students' utilisation of e-library support services in distance education has a substantial association with their learning and academic progress (Sasso, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of support services and students' technological abilities or skills are key to the success of distance learning. One of the most important support systems for guaranteeing effective online or distance education is information services (Owusu-Ansah and Bubuama, 2015;Yeboah et al, 2020). It has been suggested that students' utilisation of e-library support services in distance education has a substantial association with their learning and academic progress (Sasso, 2016).…”
Section: Introductionmentioning
confidence: 99%